Decentralized justice: state of the art, recurring criticisms and next-generation research topics - Ast, Federico; George, William; Kamalova, Jamilya; Sharma, Abeer; Aouidef, Yann (Frontiers in Blockchain, 2023)
Decentralized justice is a novel approach to online dispute resolution based on blockchain, crowdsourcing and game theory for adjudicating claims in a neutral and efficient way. Since the launch of the first decentralized justice platform in 2018, the field has attracted wide interest both from practitioners and academics in Web3 and dispute resolution. The decentralized justice approach is based on the ideas of decentralization, economic incentives and a claim to fairness in its decisions. At the current stage of development, decentralized justice is facing a number of technical, market, legal and ethical challenges for further development. This paper provides a review of the short history of decentralized justice, addresses a number of recurrent topics and lays down a path for future exploration.